EVALUASI POSTUR KERJA PADA UMKM SEPATU DENGAN METODE REPAID ENTIRE BODY ASSESMENT - Rini Halila Nasution (Universitas Harapan Medan, 2020)
Current technological developments are so rapid, so that equipment has become a basic necessity on employment. This means that equipment and technology is an important support in an effort to increase productivity for the type of work. Work posture is the determining point in analyzing the effectiveness of a job. If the work posture carried out by the operator is good and ergonomic, it can be ascertained that the results obtained will be good too. This study aims to evaluate the posture of workers in MSME shoes, where workers are too bent and their legs are bent. Therefore, this study was made so that myaman workers while doing work and can increase the productivity of these MSMEs. Assessment of work posture in this study using the REBA method, the results of the assessment of the four work positions at level 2 with information needing action for that it is necessary to propose improvement of work posture by designing work facilities such as desks and chairs.